Rare Skin Adnexal and Melanocytic Tumors Arising in Ovarian Mature Cystic Teratomas: A Report of 3 Cases and Review of the Literature. (September 2016) - Moulla, Alexandra A.; Magdy, Nesreen; Francis, Nicholas; Taube, Janis; Ronnett, Brigitte M.; El-Bahrawy, Mona
Abstract : Mature teratoma of the ovary is the most common primary ovarian tumor accounting for 15% (10%–20%) of all ovarian neoplasms. Skin and skin adnexal structures are the most common elements identified in mature teratomas. Benign and malignant skin tumors can arise in ovarian teratomas, the most common being epithelial tumors. Melanocytic and adnexal tumors developing in a teratoma are rare and can be easily overlooked. We report 3 cases and review melanocytic and skin adnexal tumors encountered in ovarian teratomas.